An Analysis Of Lecturers’ Roles And Students’ Attitudes In Classroom At Cokroaminoto Palopo University - Reski Yusrini Islamiah Yunus; Musliadi Musliadi; Paldy Paldy (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2021)
This research aimed to find out (1) the role of lecturers in the classroom in teaching English and (2) students' attitudes in the classroom during the teaching of English. The population in this study was the third-semester students of Cokroaminoto Palopo University. The researcher randomized 60 students to be 30 students as the samples and took five lecturers as the research subjects. This research used mix method with an observation checklist and questionnaire as an instrument. The data were analyzed quantitatively and qualitatively by linking the results of the instrument to the theory. The results show that the role of the lecturers in the classroom tends to influence the increase in the students learning interest in the classroom. The students have good responses to the role of the lecturers in teaching English in the classroom. Students' attitude in the classroom during the learning process tends to be active and easy to understand the material, improving thinking ability and English learning ability.